1999
DOI: 10.1038/sj.jhh.1000915
|View full text |Cite
|
Sign up to set email alerts
|

Trends in blood pressure and urinary sodium and potassium excretion in Japan: reinvestigation in the 8th year after the Intersalt Study

Abstract: Using the identical protocol of an Intersalt Study previously conducted, we undertook a new study (Intersalt-2) 8 years later. We measured changes in various factors affecting blood pressure (BP) including urinary sodium and potassium excretion in three districts of Japan: Osaka, Tochigi, and Toyama. Also we evaluated the trends in the relationships of those factors to BP.The Intersalt Study revealed that the average sodium excretion of all three study centres was high (particularly in Toyama) while potassium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…1,2 Focusing on dietary advice for individuals, salt reduction is very difficult to achieve without knowing the daily salt intake of each patient. For the evaluation of salt intake, an estimation based on sodium (Na) content in 24-h pooled urine is reliable and has been used in many clinical trials, [3][4][5][6] but this method is difficult to perform in outpatients in daily medical practice. In contrast, the evaluation of salt intake using the Na concentration in a spot urine sample is very easy to perform.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Focusing on dietary advice for individuals, salt reduction is very difficult to achieve without knowing the daily salt intake of each patient. For the evaluation of salt intake, an estimation based on sodium (Na) content in 24-h pooled urine is reliable and has been used in many clinical trials, [3][4][5][6] but this method is difficult to perform in outpatients in daily medical practice. In contrast, the evaluation of salt intake using the Na concentration in a spot urine sample is very easy to perform.…”
Section: Introductionmentioning
confidence: 99%
“…22 This methodology has been described previously. 21 The same three centres serving three districts in Japan were used as the basis for the new study. Detailed characteristics of these districts, Osaka, Tochigi and Toyama, were described in a previous study.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed characteristics of these districts, Osaka, Tochigi and Toyama, were described in a previous study. 21 To summarise, 200 people with complete measurements were recruited from each centre from each of eight sex-age strata. Within each stratum, a total of 25 people were selected at random, with one extra person selected in case one subject failed to make their appointment or to complete the 24-h urine collection procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium: 1,000 mg = 43.5 mmol *n not reported †Takemori (1997; cited by Nakagawa et al, 1999) hypothesized that the rise in sodium intake observed in the 1990s was an artefact due to a revision to the food composition tables in 1988. ‡In 1995 the survey changed from a 3-day semi-weighed record to a 1-day semi-weighed record.…”
Section: -89mentioning
confidence: 99%